Efficiency and Equity Impacts of Rural Land Rental Restrictions : Evidence from India - Deininger, Klaus; Jin, Songqing; Nagarajan, Hari K. (World Bank, Washington, DC, 2012)
Recognition of the potentially deleterious implications of inequality in opportunity originating in a skewed asset distribution has spawned considerable interest in land reforms. However, little attention has been devoted to fact that, in the longer term, the measures used to implement land reforms could negatively affect productivity. Use of state level data on rental restrictions, together with a nationally representative survey from India, suggests that, contrary to original intentions, rental restrictions negatively affect productivity and equity. The restrictions reduce the scope for efficiency-enhancing rental transactions that benefit poor producers. Simulations suggest that, by doubling the number of producers with access to land through rental, from about 15 million currently, liberalization of rental markets could have far-reaching impacts.